2021
DOI: 10.1038/s41598-021-83588-0
|View full text |Cite
|
Sign up to set email alerts
|

Vivid biofluorescence discovered in the nocturnal Springhare (Pedetidae)

Abstract: Biofluorescence has been detected in several nocturnal-crepuscular organisms from invertebrates to birds and mammals. Biofluorescence in mammals has been detected across the phylogeny, including the monotreme duck-billed platypus (Ornithorhyncus anatinus), marsupial opossums (Didelphidae), and New World placental flying squirrels (Gluacomys spp.). Here, we document vivid biofluorescence of springhare (Pedetidae) in both museum specimens and captive individuals—the first documented biofluorescence of an Old Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(91 citation statements)
references
References 42 publications
(45 reference statements)
5
69
0
Order By: Relevance
“…Some ancient reports are recalled by Pine et al [229], on the changes in color and fluorescence of the fur of wild animals after killing, when introducing its work on the various colors and fluorescence of hair of museal specimens of didelphid marsupials [229]. After that a renewed attention to the phenomenon has indicated that, in general, it seems to apply greatly to some animals with active life under poor light conditions in the crepuscular and nocturnal phases of the day, transversally representing marsupial and placental mammals in Eastern, European, American and African countries [230]. The main fluorophores described in this section are summarized in Table 9.…”
Section: Mammaliansmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ancient reports are recalled by Pine et al [229], on the changes in color and fluorescence of the fur of wild animals after killing, when introducing its work on the various colors and fluorescence of hair of museal specimens of didelphid marsupials [229]. After that a renewed attention to the phenomenon has indicated that, in general, it seems to apply greatly to some animals with active life under poor light conditions in the crepuscular and nocturnal phases of the day, transversally representing marsupial and placental mammals in Eastern, European, American and African countries [230]. The main fluorophores described in this section are summarized in Table 9.…”
Section: Mammaliansmentioning
confidence: 99%
“…In the nocturnal Pedetes surdaster and P. capensis, two springhare species belonging to the Pedetidae rodent family, an orange-red fluorescence has been detected from their fur under UV irradiation. The reddish fluorescence was proved to rise from the cuticle of the hairs, and was ascribed to porphyrins on the basis of fluorescence spectra recorded directly from the ventral and dorsal sides of the animals, besides the HPLC biochemical analysis of fur extract [230] (Figure 31).…”
Section: Mammaliansmentioning
confidence: 99%
“…As this reddish UV-PL is predominantly found in crepuscular and nocturnal species, this phenomenon has been interpreted as potentially related to visual functions for intraspeci c communication or antipredator behavior in light-deprived environments 4,8,9,24 . However, in showing that the reddish UV-PL of mammals' pelage is induced by the accumulation of photodegradable protoporphyrins, it appears more likely that this phenomenon might simply be overrepresented in crepuscular and nocturnal specimens mainly because in their case the porphyrinic compounds are less degraded than in diurnal species.…”
Section: Does Pelage Photoluminescence Have An Ecological Function?mentioning
confidence: 96%
“…The reddish UV-PL observed on the plumage of some birds was identi ed as caused by coproporphyrin III and protoporphyrin IX [20][21][22][23][24][25] , which are common molecules playing a crucial role in various biological processes and notably in heme biosynthesis 26 . A recent analysis on springhare pelage 9 identi ed a mixture of other porphyrins, usually found in urine or feces of mammals 27 , along with an unidenti ed molecule. However, the question remains whether these compounds are also responsible for the reddish UV-PL observed in other mammals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation